2004
DOI: 10.1079/phn2003553
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal assessment of the diet and growth of malnourished children participating in nutrition rehabilitation centres in Accra, Ghana

Abstract: Objective: To examine the adoption of feeding recommendations among caregivers of children recuperating from malnutrition and assess the determinants of growth of children attending a nutrition rehabilitation centre (NRC) in Accra, Ghana. Design: Longitudinal study in which attendance and maternal programme participation were recorded daily and children's anthropometry and dietary intake were measured at four time points (admission, interim, exit, post-exit) at the NRC and participants' homes. Setting: NRCs at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
23
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 11 publications
6
23
2
Order By: Relevance
“…9 Cole craft et al in a study at four day care NRCs also reported a significant increase in weight for age for the admitted children. 10 Present study showed that mean MUAC at admission was 11.8±0.7 cm and at discharge was 12.13±0.7cm. The difference was observed to be statistically highly significant (t=12.54, p<0.001).…”
Section: Discussionmentioning
confidence: 83%
“…9 Cole craft et al in a study at four day care NRCs also reported a significant increase in weight for age for the admitted children. 10 Present study showed that mean MUAC at admission was 11.8±0.7 cm and at discharge was 12.13±0.7cm. The difference was observed to be statistically highly significant (t=12.54, p<0.001).…”
Section: Discussionmentioning
confidence: 83%
“…It is normally reported that the average age at admission in centres for nutritional recovery is 12 months or less (6,17) . In the present study, no difference was found among groups of patterns of recovery and the average age at admission was 24 months, twice that reported in other studies.…”
Section: Recovery Processmentioning
confidence: 99%
“…Thus, treatment of the chronically undernourished child is necessary and perhaps is best done away from the daily living conditions, giving rise to 'daily care', but non-residential, treatment centres. However, the effectiveness of such centres on growth and maturation has rarely been reported (6,7) . Generally, national policies to fight undernutrition have consisted of food distribution to high-risk groups (e.g.…”
mentioning
confidence: 99%
“…9 Cole craft et al in a study at four day care NRCs also reported a significant increase in weight for age for the admitted children. 10 The children were on therapeutic diets F75, F100 as starter and catch up formula feeds while in NRC. Older children were given solid feeds like halwa, khichri, etc.…”
Section: Discussionmentioning
confidence: 99%